Evaluation and treatment of the infertile male - Centola, Grace M.; Ginsburg, Kenneth A. (Cambridge : Cambridge University Press, 1996)
This volume provides a comprehensive account of the evaluation and treatment of the infertile male. It is suitable for all physicians who encounter this common medical problem. Despite the prevalance of male infertility as a common underlying cause of infertility, its evaluation and treatment remains a difficult and misunderstood area for many doctors - a problem this volume aims to overcome. It includes chapters which review the full range of modern techniques now available for analysing semen and identifying the underlying cause of infertility, and then goes on to consider the various treatment options. The volume also discusses endocrine assessment and treatment, psychological aspects of male infertility, and includes a chapter on female infertility. This will be a valuable source of reference for general practitioners and physicians, urologists and gynaecologists.
1. Andrology / Grace M. Centola -- 2. Sperm-egg interaction / Don P. Wolf -- 3. Routine semen analysis / Grace M. Centola -- 4. Computer-aided sperm analysis: a critical review / Russell O. Davis and David F. Katz -- 5. Antisperm antibodies: diagnosis and treatment / Richard A. Bronson -- 6. The sperm penetration assay / B. Jane Rogers -- 7. Intrauterine insemination for male factor / William D. Schlaff and Caleb A. Awoniyi -- 8. Processing human semen for insemination: comparison of methods / William Byrd -- 9. New assays for evaluating sperm function / Lani J. Burkman -- 10. Assisted reproductive technology for male factor infertility / William R. Phipps -- 11. Microinjection techniques for male infertility / Charles C. Coddington and Sergio Oehninger -- 12. Therapeutic donor insemination: screening, indications and technique / Kenneth A. Ginsburg and Valerie Montgomery Rice -- 13. Endocrine assessment and hormone treatment of the infertile male / Rebecca Z. Sokol.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Infertility, Male